Advances in photocatalytic removal of NO_x and VOCs from flue gas - HUANG Jianghua; TAO Hengcong; CHEN Zengliang; ZHOU Mengna; JIANG Na; CHEN Xianlei*; ZHANG Xiaodong* (能源环境保护)
Nitrogen oxides (NO_x) and volatile organic compounds (VOCs) are significant precursors to particulate matter(PM_2.5) and ozone (O_3), posing serious health hazards. Photocatalytic oxidation technology is gaining increasing attention due to its mild conditions, energy efficiency, safety, and non-toxic nature. Currently, semiconductor photocatalysts, primarily based on TiO_2, exhibit unique physicochemical properties and excellent performance, becoming a focal point in current research on atmospheric pollution control. This review summarizes the latest research progress in the photocatalytic oxidation technology for the individual and simultaneous removal of NO_x and VOCs, with a focus on the potential roles of TiO_2 photocatalysts and other photocatalysts. It also explains strategies for enhancing photocatalytic activity, such as noble metal doping, non-metal doping, and semiconductor coupling. Additionally, it reviews experimental parameters, removal efficiency, and degradation mechanisms for photocatalytic degradation of flue gas NO_x and VOCs. This review aims to summarize the structure-performance-application relationship in the development of semiconductor photocatalytic materials, provide parameter support and optimization suggestions for research on the simultaneous removal of flue gas NO_x and VOCs, discuss new catalyst preparation and modification approaches, and promote future research on the co-removal of NO_x and VOCs by photocatalytic oxidation.